Dampak Shopee Live, Online Customer Review, dan Video Content Marketing terhadap Keputusan Pembelian pada Aneka Jersey - Risma Nur Ariyana Putri; Budi Santoso; Achmad Hasan Hafidzi (Universitas Nusantara PGRI Kediri, 2025)
The rapid development of technology in the current digital era has affected many areas of life. The rise of online markets has changed the way consumers shop, shifting from traditional face-to-face transactions to online purchases. This study aims to investigate and examine how Shopee Live, online customer feedback, and video content marketing influence consumer purchasing choices related to products offered by Aneka Jersey. With a sample of 170 participants, this study uses an associative quantitative method. Data collection was mostly done through questionnaires, the sampling technique was non-probability sampling with a purposeful sampling approach. In data analysis, this study used various stages, including instrument testing, classical assumption testing, conducting multiple linear regression analysis, conducting hypothesis testing, and calculating the coefficient of determination. The research findings show that Shopee Live, online customer reviews, and video content marketing positively and significantly influence purchasing choices related to Aneka Jersey products. The coefficient of determination (R²) shows that there is a contribution of 32.1% to the variables related to purchasing decisions.